Individual differences in GHB consumption in a new voluntary GHB self-administration model in outbred rats - Casper J. H. Wolf; Marcia Spoelder; Harmen Beurmanjer; Ronald Bulthuis; Arnt F. A. Schellekens; Judith R. Homberg (Psychopharmacology, 2024)
Background and purpose The use of the recreational drug gamma-hydroxybutyric acid (GHB) has increased over the past decade, concomitantly leading to a higher incidence of GHB use disorder. Evidence-based treatment interventions are hardly available and cognitive effects of long-term GHB use remain elusive. In order to study the development of GUD and the causal effects of chronic GHB consumption, a GHB self-administration model is required. Experimental approach Long Evans rats had access to GHB in their home cage according to a two-bottle choice procedure for 3 months. Intoxication and withdrawal symptoms were assessed using an automated sensor-based setup for longitudinal behavioral monitoring. Rats were trained in an operant environment according to a fixed ratio (FR) 1, 2, and 4 schedule of reinforcement. Addiction-like behaviors were assessed through progressive ratio-, non-reinforced-, and quinine-adulterated operant tests. In addition, the novel object recognition test and elevated plus maze test were performed before and after GHB self-administration to assess memory performance and anxiety-like behavior, respectively. Key results All rats consumed pharmacologically relevant levels of GHB in their home cage, and their intake remained stable over a period of 3 months. No clear withdrawal symptoms were observed following abstinence. Responding under operant conditions was characterized by strong inter-individual differences, where only a subset of rats showed high motivation for GHB, habitual GHB-seeking, and/or continued responding for GHB despite an aversive taste. Male rats showed a reduction in long-term memory performance 3 months after home-cage GHB self-administration. Anxiety-like behavior was not affected by GHB self-administration. Conclusion and implications The GHB self-administration model was able to reflect individual susceptibility for addiction-like behavior. The reduction in long-term memory performance upon GHB self-administration calls for further research into the cognitive effects of chronic GHB use in humans.

Use of Our Future Seas: Relevance of Spatial and Temporal Scale for Physical and Biological Indicators - Neda Trifonova; Beth Scott; Michela De Dominicis; Judith Wolf (Frontiers in Marine Science, 2022)
There is about to be an abrupt step-change in the use of our coastal seas, specifically by the addition of large-scale offshore renewable energy developments to combat climate change. Many trade-offs will need to be weighed up for the future sustainable management of marine ecosystems between renewables and other uses (e.g., fisheries, marine protected areas). Therefore, we need a much greater understanding of how different marine habitats and ecosystems are likely to change with both natural and anthropogenic transformations. This work will present a review of predictive Bayesian approaches from ecosystem level, through to fine scale mechanistic understanding of foraging success by individual species, to identify consistent physical (e.g., bottom temperature) and biological (e.g., chlorophyll- a ) indicators of habitat and ecosystem change over the last 30 years within the North Sea. These combined approaches illuminate the feasibility of integrating knowledge across scales to be able to address the spatio-temporal variability of biophysical indicators to ultimately strengthen predictions of population changes at ecosystem scales across broadly different habitat types. Such knowledge will provide an effective baseline for more strategic and integrated approaches to both monitoring studies and assessing anthropogenic impacts to be used within marine spatial planning considerations.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Mangrove Loss and Gain in a Densely Populated Urban Estuary: Lessons From the Guangdong-Hong Kong-Macao Greater Bay Area - Heng Wang; Yisheng Peng; Chen Wang; Qingke Wen; Jinyong Xu; Zhan Hu; Xing Jia; Xuemei Zhao; Weihang Lian; Stijn Temmerman; Judith Wolf; Tjeerd Bouma (Frontiers in Marine Science, 2021)
Understanding the recent changes in mangrove adjacent to mega-cities is critical for conservation, management, and policymaking in coastal zones with fast population growth and global change. Here we investigated mangrove area changes in one of the world’s largest urban areas near the main estuaries in the Guangdong-Hong Kong-Macao Greater Bay Area (GBA). Mangrove area changes are quantified for the period 1990–2018 by analyzing multiple sources of satellite images by classification algorithms. We found that estuarine mangrove area dynamics are driven by human actions and are contrasting between these two periods. (1) During 1990–2000, the estuarine mangrove area approximately decreased from 11.5 to 6.9 km 2 , among which the bulk part was transformed into aquaculture ponds (41.1%) and built-up area (29.9%). (2) During 2000–2018, the estuarine mangrove area rapidly increased to 18.3 km 2 resulting from the protection and restoration efforts. Proportions of mangrove occurring in nature reserves increased from 37.5% in 1990 to >80% in the 2000s. Two major mangrove expansion ways, natural establishment (NE, in protected areas without any human interference) and human afforestation (HA) accounted almost equally (53.1 and 46.9%) for the gained estuarine mangrove area during 2010–2018. A future projection according to the current mangrove increasing rate suggests that all the low-lying land that is theoretically suitable for mangrove afforestation would be used up by 2060. Although afforestation has contributed to important gains in mangrove quantity, we highlight that it may also imply decreased habitat quality. It has resulted in a great occupation of high tidal mudflats and a loss of their valuable ecosystem services, and it may lead to spreading of non-native species, e.g., Sonneratia apetala , used in afforestation programs. Future restoration approaches should adopt more eco-friendly strategies, like reversing (abandoned) aquaculture ponds to native mangrove forests. Knowledge obtained from the GBA in this study may be also instrumental to ecological restorations for mangrove forests in other urbanized estuaries.

“Grey swan” storm surges pose a greater coastal flood hazard than climate change - Kevin Horsburgh; Ivan D. Haigh; Jane Williams; Michela De Dominicis; Judith Wolf; Addina Inayatillah; David Byrne (Ocean Dynamics, 2021)
In this paper, we show that over the next few decades, the natural variability of mid-latitude storm systems is likely to be a more important driver of coastal extreme sea levels than either mean sea level rise or climatically induced changes to storminess. Due to their episodic nature, the variability of local sea level response, and our short observational record, understanding the natural variability of storm surges is at least as important as understanding projected long-term mean sea level changes due to global warming. Using the December 2013 North Atlantic Storm Xaver as a baseline, we used a meteorological forecast modification tool to create “grey swan” events, whilst maintaining key physical properties of the storm system. Here we define “grey swan” to mean an event which is expected on the grounds of natural variability but is not within the observational record. For each of these synthesised storm events, we simulated storm tides and waves in the North Sea using hydrodynamic models that are routinely used in operational forecasting systems. The grey swan storms produced storm surges that were consistently higher than those experienced during the December 2013 event at all analysed tide gauge locations along the UK east coast. The additional storm surge elevations obtained in our simulations are comparable to high-end projected mean sea level rises for the year 2100 for the European coastline. Our results indicate strongly that mid-latitude storms, capable of generating more extreme storm surges and waves than ever observed, are likely due to natural variability. We confirmed previous observations that more extreme storm surges in semi-enclosed basins can be caused by slowing down the speed of movement of the storm, and we provide a novel explanation in terms of slower storm propagation allowing the dynamical response to approach equilibrium. We did not find any significant changes to maximum wave heights at the coast, with changes largely confined to deeper water. Many other regions of the world experience storm surges driven by mid-latitude weather systems. Our approach could therefore be adopted more widely to identify physically plausible, low probability, potentially catastrophic coastal flood events and to assist with major incident planning.

Tide-Surge Interaction in the Pearl River Estuary: A Case Study of Typhoon Hato - Peng Zheng; Ming Li; Caixia Wang; Judith Wolf; Xueen Chen; Michela De Dominicis; Peng Yao; Zhan Hu (Frontiers in Marine Science, 2020)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Variability of nutrients and carbon dioxide in the Antarctic Intermediate Water between 1990 and 2014 - Essowè Panassa; J. Magdalena Santana-Casiano; Melchor González-Dávila; Mario Hoppema; Steven M.A.C van Heuven; Christoph Völker; Dieter Wolf-Gladrow; Judith Hauck (Ocean Dynamics, 2018)

Preface: Oceanographic processes on the continental shelf: observations and modeling - Sandro Carniel; Judith Wolf; Vittorio E. Brando; Lakshmi H. Kantha (Ocean Science, 2017)

Flagship umbrella species needed for the conservation of overlooked aquatic biodiversity - Gregor Kalinkat; Juliano S. Cabral; William Darwall; G. Francesco Ficetola; Judith L. Fisher; Darren P. Giling; Marie‐Pierre Gosselin; Hans‐Peter Grossart; Sonja C. Jähnig; Jonathan M. Jeschke; Klaus Knopf; Stefano Larsen; et al. (Conservation Biology, 2017)

Blue Carbon Stock of the Bangladesh Sundarban Mangroves: What could Be the Scenario after a Century? - Abhra Chanda; Anirban Mukhopadhyay; Tuhin Ghosh; Anirban Akhand; Parimal Mondal; Subhajit Ghosh; Sandip Mukherjee; Judith Wolf; Attila N. Lázár; Md. Munsur Rahman; Mashfiqus Salehin; S. M. Chowdhury; et al. (Wetlands, 2016)

Meteorology and oceanography of the Atlantic sector of the Southern Ocean—a review of German achievements from the last decade - Hartmut H. Hellmer; Monika Rhein; Günther Heinemann; Janna Abalichin; Wafa Abouchami; Oliver Baars; Ulrich Cubasch; Klaus Dethloff; Lars Ebner; Eberhard Fahrbach; Martin Frank; Gereon Gollan; et al. (Ocean Dynamics, 2016)

Projected changes in area of the Sundarban mangrove forest in Bangladesh due to SLR by 2100 - Andres Payo; Anirban Mukhopadhyay; Sugata Hazra; Tuhin Ghosh; Subhajit Ghosh; Sally Brown; Robert J. Nicholls; Lucy Bricheno; Judith Wolf; Susan Kay; Attila N. Lázár; Anisul Haque (Climatic Change, 2016)

Past to future extreme events in Liverpool Bay: model projections from 1960–2100 - Jennifer M. Brown; Judith Wolf; Alejandro J. Souza (Climatic Change, 2012)

The Tyndall coastal simulator - Mustafa Mokrech; Susan Hanson; Robert J. Nicholls; Judith Wolf; Mike Walkden; Corentin M. Fontaine; Sophie Nicholson-Cole; Simon R. Jude; James Leake; Peter Stansby; Andrew R. Watkinson; Mark D. A. Rounsevell; et al. (Journal of Coastal Conservation, 2011)

Numerical investigation of wave propagation in the Liverpool Bay, NW England - Ming Li; Ip Raymond; Judith Wolf; Xueen Chen; Richard Burrows (Acta Oceanologica Sinica, 2011)

The wave climate of Liverpool Bay—observations and modelling - Judith Wolf; Jennifer Mary Brown; Michael John Howarth (Ocean Dynamics, 2011)

Surge modelling in the eastern Irish Sea: present and future storm impact - Jenny M. Brown; Alejandro J. Souza; Judith Wolf (Ocean Dynamics, 2010)

Modelling of waves in the Irish Sea: effects of oceanic wave and wind forcing - Shunqi Pan; Yongping Chen; Judith Wolf; Yanliang Du (Ocean Dynamics, 2009)

Coastal flooding: impacts of coupled wave–surge–tide models - Judith Wolf (Natural Hazards, 2009)

Factors affecting proliferation and dedifferentiation of primary bovine oviduct epithelial cells in vitro - Judith Reischl; Katja Prelle; Heidrun Schöl; Christine Neumüller; Ralf Einspanier; Fred Sinowatz; E. Wolf (Cell and Tissue Research, 1999)